2021
DOI: 10.1038/s41598-021-97976-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Staphylococcus pseudintermedius in cats in Poland

Abstract: Staphylococcus pseudintermedius is a well-known coagulase-positive staphylococcus that is mainly associated with the asymptomatic colonization of the skin of pets and mucous membranes. Little is still known about the occurrence of S. pseudintermedius in cats. The current study aimed to characterize the isolates of S. pseudintermedius from sick and healthy cats. This was achieved by examining their antibiotic resistance properties, biofilm formation, and genotype differences. Six hundred and seventy-six cats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 40 publications
(47 reference statements)
5
17
1
Order By: Relevance
“…Seriously, two colonies of MSSP were obtained from the surgical environment in the present study, although this environment is expected to be sterile to prevent surgical site infections. Staphylococci contamination of the surgical environment is occasionally found in veterinary hospitals and may cause surgical site infections [ 2 , 32 ]. Fortunately, S. pseudintermedius infection was not observed in any of the dogs operated in this hospital (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Seriously, two colonies of MSSP were obtained from the surgical environment in the present study, although this environment is expected to be sterile to prevent surgical site infections. Staphylococci contamination of the surgical environment is occasionally found in veterinary hospitals and may cause surgical site infections [ 2 , 32 ]. Fortunately, S. pseudintermedius infection was not observed in any of the dogs operated in this hospital (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial pyoderma is mainly associated with coagulase-positive staphylococci. In dogs, S. aureus may be responsible for up to 10% of pyoderma cases [2], whereas in cats, it is often associated with a higher proportion of cases [4,24]. This difference in the frequency rate of S. aureus between cats and dogs may reflect the lower adherence of S. pseudintermedius to feline corneocytes when compared to canine corneocytes [25].…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, Staphylococcus pseudintermedius accounts for nearly 90% of pyoderma cases, whereas Staphylococcus aureus and Staphylococcus coagulans are interchangeably the second most common pathogen accounting for up to 10% of pyoderma cases [2,3]. In cats, S. aureus is a more frequent agent of pyoderma than S. pseudintermedius, although there is less available literature for these cases [4]. The prevalence rate of these bacterial pathogens in other companion animals, such as rabbits, is relatively unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, our findings were consistent with those of a previous study by Polish researchers. Bierowiec et al reported that S. pseudintermedius is the least prevalent bacteria in cats among the Staphylococcus class of bacteria [ 9 ]. In previous reports, the prevalence of S. pseudintermedius in dogs was 90%, which is higher than that in cats with a prevalence range of 2.49–8.8% [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%